2003
DOI: 10.1016/s0014-5793(03)00179-0
|View full text |Cite
|
Sign up to set email alerts
|

Activation mechanism of c‐Jun amino‐terminal kinase in the course of endodermal differentiation of P19 embryonic carcinoma cells

Abstract: c-Jun amino-terminal kinase (JNK) is known to be activated and play critical roles during neural and endodermal di¡erentiation of P19 embryonic carcinoma cells. In this study we demonstrated that of the two upstream protein kinases of JNK, only MKK4 activity was substantially enhanced in the endodermally di¡erentiating P19 cells. This enhanced activity of MKK4 stemmed from the increased expression of MKK4 and its activation by phosphorylation. Activated MKK4 and JNK were localized in both nucleus and cytoplasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2004
2004
2007
2007

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…We have also shown that MKK4 but not MKK7 was activated in the course of the RA-induced primitive endodermal differentiation of P19 cells (26). These observations suggest that the activation of MKK4 but not MKK7 serves as the common mechanism of JNK activation in both the neural and the primitive endodermal differentiation of P19 cells.…”
Section: Discussionsupporting
confidence: 53%
“…We have also shown that MKK4 but not MKK7 was activated in the course of the RA-induced primitive endodermal differentiation of P19 cells (26). These observations suggest that the activation of MKK4 but not MKK7 serves as the common mechanism of JNK activation in both the neural and the primitive endodermal differentiation of P19 cells.…”
Section: Discussionsupporting
confidence: 53%
“…While phospho-MAP2K3/MAP2K6 proteins were detected in the cytoplasm and the nucleus, phospho-MAP2K4 proteins were confined to the nuclei, suggesting that p38 MAPK phosphorylation by MAP2K4 may occur predominantly in the nucleus. This nuclear localization is supported by studies that investigated the activation of JNK/SAPK in P19 embryonic carcinoma cells [28]. MAP2K4 was detected in both the nucleus and cytoplasm of differentiated P19 cells, but only in the nucleus of undifferentiated P19 cells [28].…”
Section: Discussionmentioning
confidence: 60%
“…This nuclear localization is supported by studies that investigated the activation of JNK/SAPK in P19 embryonic carcinoma cells [28]. MAP2K4 was detected in both the nucleus and cytoplasm of differentiated P19 cells, but only in the nucleus of undifferentiated P19 cells [28]. Other studies have established that JNK/SAPK and MAP2K4 are activated and translocated into the nucleus in response to cellular stress [29,30].…”
Section: Discussionmentioning
confidence: 64%